C1orf194 deficiency leads to incomplete early embryonic lethality and dominant intermediate Charcot–Marie–Tooth disease in a knockout mouse model. (27th June 2020) - Huang, Cheng; Shen, Zong Rui; Huang, Jin; Sun, Shun Chang; Ma, Di; Li, Mei Yi; Wang, Zhi Kui; Zheng, Ying Chun; Zheng, Zhuo Jun; He, Fei; Xu, Xiaoyuan; Li, Ziang; et al.
Abstract: Charcot–Marie–Tooth (CMT) disease is the most common inherited peripheral neuropathy and shows clinical and genetic heterogeneity. Mutations in C1orf194 encoding a Ca 2+ regulator in neurons and Schwann cells have been reported previously by us to cause CMT disease. In here, we further investigated the function and pathogenic mechanism of C1or194 by generating C1orf194 knockout (KO) mice. Homozygous mutants of C1orf194 mice exhibited incomplete embryonic lethality, characterized by differentiation abnormalities and stillbirth on embryonic days 7.5–15.5. Heterozygous and surviving homozygous C1orf194 KO mice developed motor and sensory defects at the age of 4 months. Electrophysiologic recordings showed decreased compound muscle action potential and motor nerve conduction velocity in the sciatic nerve of C1orf194 -deficient mice as a pathologic feature of dominant intermediate-type CMT. Transmission electron microscopy analysis revealed demyelination and axonal atrophy in the sciatic nerve as well as swelling and loss of mitochondrial matrix and other abnormalities in axons and Schwann cells. A histopathologic examination showed a loss of motor neurons in the anterior horn of the spinal cord and muscle atrophy. Shorter internodal length between nodes of Ranvier and Schmidt–Lanterman incisures was detected in the sciatic nerve of affected animals. These results indicate that C1orf194 KO mice can serve as an animal model of CMT with a severe dominant intermediate CMT phenotype that can be used to investigate the molecular mechanisms of the disease and evaluate the efficacy of therapeutic strategies.